Protective performance test and safety risk evaluation of a powered air-purifying suit - Limei Hao; Jiancheng Qi; Runze Wang; Ying Yi; Jinhui Wu (Elsevier, 2019)
The positive pressure biological protective suit is the highest degree of personal protective equipment, and its performance directly impacts the health and safety of the wearer. Protection factor is the most critical measure of the performance of a positive pressure bio-protective suit. This study establishes a dynamic detection system for the positive pressure bio-protective suit, to evaluate its safety risks, and explores methods to reduce these risks. A manikin was used to perform human actions, such as raising the arms, sitting, and walking, that were simulated at different levels. Integrity breaches of different shapes and sizes were made to different parts of the suit for evaluation. The aerosol concentration and the pressure of the suit were detected. Positive-pressure suits provide exceptionally good protection even in accident scenarios and provide a greater flexibility and more ergonomic benefits. However, sufficiently large (>3 cm) breaches caused a negative-pressure and an inward airflow during vigorous activities. The location of the breach site on the suit also had a significant effect on bio-aerosol leakage. Studies have shown that effective methods to avoid the risk of damage include increasing the air supply flow and performing gentle movements while wearing the suit. The dynamic detection method and the results obtained in this study are a significant advance to predict and avoid the risks associated with powered air-purifying suits.